The Impact of Digital Transformation on MSME Competitiveness and Economic Growth - Aisyah Chusnul Jurnalita (LifeSciFi, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in economic development by driving job creation and contributing to GDP growth. The rapid advancement of digital technology has transformed the business landscape, providing MSMEs with opportunities to enhance their competitiveness. This study examines the impact of digital transformation on MSMEs, focusing on the adoption of e-commerce platforms, financial technology (fintech), and digital marketing strategies. The findings indicate that digital tools enable MSMEs to expand their market reach, improve operational efficiency, and respond effectively to changing consumer behavior. However, challenges such as limited digital literacy, inadequate internet infrastructure, and high adoption costs hinder full digital integration. To optimize the benefits of digital transformation, policymakers and stakeholders must support MSMEs through financial assistance, training programs, and improved digital infrastructure. This study highlights the need for a collaborative approach between government, industry, and academia to foster a sustainable digital ecosystem for MSMEs, ensuring their resilience and long-term growth in an increasingly digital economy.